2020
DOI: 10.1200/jco.2020.38.15_suppl.5544
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab (pembro) plus olaparib in patients (pts) with docetaxel-pretreated metastatic castration-resistant prostate cancer (mCRPC): KEYNOTE-365 cohort A efficacy, safety, and biomarker results.

Abstract: 5544 Background: Pembro + olaparib has shown antitumor activity and acceptable safety in docetaxel-pretreated pts with mCRPC enrolled in cohort A of the phase I/II KEYNOTE-365 study (NCT02861573). Updated results with new biomarker data are reported. Methods: Pts with docetaxel-pretreated mCRPC who progressed within 6 mo of screening received pembro 200 mg IV Q3W + olaparib 400-mg capsule or 300-mg tablet PO BID. Pts might have received 1 other chemotherapy and ≤2 second-generation androgen-receptor targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The most promising strategies for mCRPC treatment combining of two different checkpoint inhibitors or combining one checkpoint inhibitor with enzalutamide, an anti-androgen approved for use in mCRPC [124][125][126]. Recent studies investigating the combination of anti-PD-1 and anti-CTLA4 had promising results in phase I/II and III [127][128][129] with the autologous cellular immunotherapy sipuleucel-T [130]. This treatment consists of autologous peripheral blood mononuclear cells, including antigen-presenting cells, which are previously activated with a recombinant fusion protein that is a prostate antigen fused to granulocyte-macrophage colony-stimulating factor, an immune-cell activator [131,132].…”
Section: Recent Immunotherapy Clinical Trials In Prostate Cancermentioning
confidence: 99%
“…The most promising strategies for mCRPC treatment combining of two different checkpoint inhibitors or combining one checkpoint inhibitor with enzalutamide, an anti-androgen approved for use in mCRPC [124][125][126]. Recent studies investigating the combination of anti-PD-1 and anti-CTLA4 had promising results in phase I/II and III [127][128][129] with the autologous cellular immunotherapy sipuleucel-T [130]. This treatment consists of autologous peripheral blood mononuclear cells, including antigen-presenting cells, which are previously activated with a recombinant fusion protein that is a prostate antigen fused to granulocyte-macrophage colony-stimulating factor, an immune-cell activator [131,132].…”
Section: Recent Immunotherapy Clinical Trials In Prostate Cancermentioning
confidence: 99%
“…The authors, therefore, concluded that these data provided rationale to evaluate combined PARP and immune checkpoint inhibition in BRCA / PALB2 -mutated PDAC patients [ 124 ]. This approach is now showing early promise in ovarian [ 125 ], prostate [ 126 ] and lung cancers [ 127 ]. As mentioned, this approach is now under evaluation in PDAC, including a phase 2 trial evaluating the combination of Pembrolizumab and Olaparib [ 128 ], though this trial and the many similar ongoing studies have yet to post results.…”
Section: Summary and Future Directionmentioning
confidence: 99%
“…One such strategy, investigated in several clinical trials, involves combining immune checkpoint inhibitors with other anticancer treatments that have the potential to stimulate an increasingly immune-responsive prostate cancer microenvironment, testing the hypothesis that the immunotherapeutic effects will be augmented and outcomes improved. [4][5][6][7] This combination approach is necessary because treatment with single-agent immune checkpoint inhibitors targeting the anti-programmed death-1 (PD-1)/programmed death ligand 1 (PD-L1) pathway does not appear to elicit clinically impactful antitumor responses in unselected mCRPC populations. [8][9][10][11] Although pivotal trials of ipilimumab (a cytotoxic T-lymphocyte antigen-4 checkpoint inhibitor) monotherapy originally failed to show improvements in overall survival (OS) versus placebo for unselected patients with mCRPC, 12 13 an excess of long-term survivors versus placebo has since been reported in this clinical setting.…”
Section: What This Study Addsmentioning
confidence: 99%